A functional variant of miRNA‐149 confers risk for allergic rhinitis and comorbid asthma in Chinese children. (8th February 2017) - Hu, D.; Zhang, Z.; Ke, X.; Kang, H.; Hong, S.
Summary: The prevalence of allergic rhinitis (AR) and asthma has been increasing, and the comorbidity rates of these diseases are very high. Here, 176 AR patients, 124 patients with comorbid AR and asthma (AR‐A) and 206 healthy Chinese children as controls were included in a case–control study. Six single‐nucleotide polymorphisms (SNPs), miR‐146a (rs2910164, rs57095329 and rs6864584), miR‐196a2 (rs11614913), miR‐499 (rs3746444) and miR‐149 (rs2292832), were genotyped. The prevalence of homozygous miR‐149 (rs2292832) CC genotype and C allele were considerably increased in AR and AR‐A patients, compared with the controls. AR‐A group showed higher frequencies of CC genotype and C allele of rs2292832 than AR group. No significant difference in the genotypic and allelic frequencies of other miRNA SNPs was found between the groups. MiR‐149 levels in peripheral blood mononuclear cells (PBMCs) were significantly lower in CC (variant type) cases compared with TT ( wild‐type ) cases. In further experiments, PBMCs obtained from the healthy controls with CC, CT and TT genotypes were stimulated by house dust mite extracts, which led to a significant decrease in the levels of miR‐149 in PBMCs obtained from CC and TT individuals. This decrease was more pronounced in CC compared with TT cases. Our results demonstrate that miR‐149 rs2292832 variant is not only strongly associated with AR and AR‐A, but it may lead to an increase in the susceptibility to allergies following the stimulation with an allergen, through the changes in miR149 expression. Additionally, AR patients with CC genotypes were shown to be more susceptible to asthma.